Perancangan Jaringan LTE – Advanced Menggunakan Metode Carrier Aggregation Inter Band Non – Contiguous Di Kabupaten Kampar - Danny Wijaya; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Long Term Evolution Advanced (LTE-A) is a network technology that allows LTE networks to run on two different frequencies. This network speed of LTE – A can reach up to 1 Gbps. In Indonesia there are limitations of network frequency allocation. So, network design options are made by combining frequency and bandwidth on the network. The purpose of this study is to design an LTE-Advanced network with the Carrier Aggregation (CA) method. CA is a method that can combine two or more components of a carrier with maximum bandwidth of 20 MHz. In Kampar Regency itself there is no implementation of the LTE-Advanced network. In this research the design of the LTE-A network uses the interband-non-contiguous CA method. After getting the results, a network comparison is made between using CA or without the CA method based on planning by coverage and planning by capacity. The frequency bands used are 900 MHz and 1800 MHz with a total bandwidth of 15 MHz. Parameter test results show that. Coverage by signal level in non-CA method at 900 MHz frequency 5 Mhz bandwidth has a value of 99.83% on signal level >80 dBm, while at 1800 MHz frequency 10 MHz bandwidth has a value of 99,85% at the signal >80 level dBm. On the other side Coverage by signal level on CA frequency 900 & 1800 MHz with a total bandwidth of 15 MHz is superior at 99.97% with a signal value of >80 dBm. So that it can be concluded that the design with CA techniques has superior value compared to Non-CA.Keywords: Advanced LTE, carrier aggregation, planning by coverage, planning by capacity, bandwidth, signal level.